The Intricate Crosstalk Between Insulin and Pancreatic Ductal Adenocarcinoma: A Review From Clinical to Molecular - Deng, Junyuan; Guo, Yujie; Du, Jiali; Gu, Jichun; Kong, Lei; Tao, Boan; Li, Ji; Fu, Deliang (Frontiers in Cell and Developmental Biology, 2022)
Increased insulin level (or "hyperinsulinemia") is common in pancreatic cancer patients and signals poor clinical outcomes. Clinical and laboratory studies revealed that insulin is safe for the long-standing diabetes population but increases pancreatic cancer risk in high-risk populations. The intrinsic relationship between insulin and pancreatic cancer (PDA) is bidirectional. Pancreatic cancer synthesizes multiple molecules to induce peripheral insulin resistance and delay insulin secretion in PDA patients. As a result, both hyperinsulinemia and hyperglycemia occur in PDA patients. Reversely, insulin promotes the initiation of pancreatic cancer and sustains tumor survival by eliciting tumorigenic inflammation, lipid and glucose metabolic reprogram, overcoming apoptosis and chemotherapies through crosstalk with IGF-1, and stimulating invasion with metastases, and activating tumor microenvironment formation (inflammation, fibrosis, and angiogenesis). Currently, taking other antidiabetic drugs is an effective way of lowering blood glucose and insulin level at the same time. And drugs targeting insulin-related signal pathways may pave a novel method for suppressing PDA initiation and progression.